A utilização das imagens de radar meteorológico em Climatologia - Fragoso, Marcelo (1996)
WEATHER RADAR IMAGE IN CLIMATOLOGY - After a brief overview about weather radar as a remote sensing instrument, some problems concerning the use of radar images are discussed. The great interest of radar images as a tool in Climatology is pointed out. Finally, a case study about two rainfall events in Nancy (France) in April 1995 is presented.